Intradiscal electrothermal therapy for chronic discogenic low back pain: a comparison of two heating protocols - Ökmen, Korgün; Metin Ökmen, Burcu (The European Research Journal, 2018)
Objectives. This study aims to evaluate the effect of intradiscal electrothermal therapy (IDET) applied in patients with chronic low back pain using two heating protocols. Methods. In this study, data of 50 patients who were exposed to percutaneous IDET using two heating protocols were retrospectively analyzed. The patients were divided into two groups: in Group 1 (n=25), maximum 750C catheter tipping was used, while in Group 2 (n=25), maximum 900C catheter tipping was performing. Pre-treatment (M0) and post-treatment results at 3 (M3), 6 (M6), 12 (M12), and 18 months (M18) were evaluated using the visual analogue acale (VAS), Oswestry disability index (ODI), and short form-36 (SF-36) scores.Results. There was no statistically significant difference in demografic characteristics and M0 VAS, ODI values and SF-36 dimensions of the patients between the groups (p > 0.05). It was found that there were statistically significant improvement than baseline values in the M3, M6, M12, and M18 VAS, ODI, and SF-36 scores in both treatment groups (p < 0.05). Between the group comparison; only the M18 VAS and SF-36 pain values were found statistically significant in the positive direction in Group 2 (p < 0.05). Conclusion. Similar successful results were obtained in our study involving two different heating procedures up to 12 months of administering IDET treatment. But at the 18th month the 900C IDET seems to be more effective in improving the pain scores.